Validity and Reliability of a Smartphone and Digital Inclinometer in Measuring the Lower Extremity Joints Range of Motion - Walaa S. Mohammad; Faten F. Elattar; Walaa M. Elsais; Salameh O. AlDajah (Montenegrin Sports Academy, 2021)
In clinical settings, available valid and reliable tools are important components in evaluating the lower extremity range of motion. Although the digital inclinometer is highly reliable compared to the universal goniometer, its availability and high cost impede its extensive use. Nowadays, smartphone applications have become widely available to clinicians for assessing the joint range of motion. The present study aims to assess the validity and intra-rater reliability of the smart- phone application "Clinometer" for measuring hip, knee, and ankle sagittal ranges of motion, using the digital inclinom- eter as the reference standard. Active hip, knee flexion and ankle dorsiflexion and plantarflexion range-of-motion mea- surements were recorded in 102 young, healthy female participants on two separate occasions using Clinometer and a digital inclinometer. Pearson's correlation coefficients (r) were used to evaluate the smartphone application's validity against the digital inclinometer. To assess the reliability of the Clinometer app, the intra-class correlation coefficient (ICC), standard error of measurement (SEM), and minimal detectable difference (MDD) were used. Clinometer displayed excellent validity when compared to the digital inclinometer for hip and knee movements (r>0.90), while ankle ROM displayed moderate validity (r = 0.52-0.57). Additionally, Clinometer demonstrated excellent reliability (ICC > 0.90) for hip and knee sagittal plane motion and moderate reliability for the ankle sagittal plane motion (ICC = 0.53-0.67). Cli- nometer is a portable, low-cost, valid, and reliable tool for assessing active hip and knee range of motions and can be easily incorporated into clinical settings; however, it cannot be used interchangeably for ankle measures.